Strategy: planning for competitive edge 1 - May, Gary (Henry Stewart Talks, 2011)
The internal and external strategic processes, Benefits of strategic planning, Establishing your vision, Clarifying your mission, Articulating core values, Non-profit mentoring organization, Vision-mission-value responsibility, General environment factors, Various trends, Porter's five-forces analysis, The threat of new entrants and substitute products- Bargaining power of suppliers & buyers, Rivalry among existing firms, Competitor analysis, Resource analysis, Competitive advantage, Analysis of strengths and weaknesses, Value chain analysis